The vaccination approach to control infections leading to dental caries - Renata O. Mattos-Graner; Daniel J. Smith (Universidade Estadual de Campinas, 2015)
Dental caries is a transmissible infectious disease, in which mutans streptococci (MS) play the role of main pathogens. This oral disease represents a public health problem worldwide, and despite the advances in dental health with the use of fluoride abroad, treatment of caries manifestations and their outcomes are still highly costly to public and private healthcare systems. Lack of treatment of dental caries ultimately may have serious systemic consequences. Mutans streptococci have a panel of virulence factors important for their establishment in the complex microbial community of the dental biofilm and in the induction of caries. In this review we discuss the advances in our understanding of the molecular mechanisms which underlie MS transmission, tooth colonization and virulence. Infection and disease take place in a milieu exposed to components of the mucosal and systemic immune systems of the host. Thus, inducing host responses which target aspects of mutans streptococcal colonization and disease may provide additional measures to modify dental caries. This review also describes current strategies for anti-caries vaccination efforts with regard to important bacterial targets, routes, adjuvants and delivery systems for active and passive immunization.